2017
DOI: 10.15761/jts.1000193
|View full text |Cite
|
Sign up to set email alerts
|

Cases of psoriasis improved by lowering homocysteine using 4-7 mg folic acid, vitamins B6 and B12 previously worsened using 1-2 mg daily folic acid, B6 and B12 folic acid

Abstract: The daily intake of FA of 5% Americans age 50 and over and in one study of psoriatic American women is about 1 mg. A patient with plaque psoriasis on 10 mg lisinopril did not improve on vitamins B12 and B6 alone. When folic acid 5 mg daily was added PASI improved 50%. Three cases of plaque psoriasis flared when given 1-2 mg folic acid (FA), 100 mg vitamin B6 and 1000 mcg daily B12. When daily FA was increased to 4 to 7 mg daily all three cases improved their disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…High levels of folic acid and vitamin B12 are known to improve the pathological condition related to psoriasis. 57 As reported in Table 2 , our data indicated low levels of folic acid and vitamin B12 at T0, whereas an increase in the concentration was registered at T1. Hypocalcemia was observed as a risk factor in psoriasis.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…High levels of folic acid and vitamin B12 are known to improve the pathological condition related to psoriasis. 57 As reported in Table 2 , our data indicated low levels of folic acid and vitamin B12 at T0, whereas an increase in the concentration was registered at T1. Hypocalcemia was observed as a risk factor in psoriasis.…”
Section: Discussionsupporting
confidence: 70%
“…Biochemical and clinical parameters indicated a general improvement in the metabolites’ concentration known to be related to the condition of psoriasis: folic acid, vitamin B12, calcium, bilirubin, cortisol, LDL, and total cholesterol. High levels of folic acid and vitamin B12 are known to improve the pathological condition related to psoriasis . As reported in Table , our data indicated low levels of folic acid and vitamin B12 at T0, whereas an increase in the concentration was registered at T1.…”
Section: Discussionmentioning
confidence: 97%
“…The results indicate neither a beneficial nor an adverse effect. Aronson [125] reported that a patient with plaque psoriasis on 10 mg lisinopril did not improve on vitamins B12 and B6 alone. When folic acid (FA) 5 mg daily was added PASI improved by 50%.…”
Section: Targeting Hcy As a Strategy For Treatment Of Psoriasismentioning
confidence: 99%
“…Moreover, a significant reduction in the standard parameters was recorded (DLQI, VAS pain, and VAS pruritus), while PASI scores showed a significant 50% reduction [ 7 ]. Ps is known to lead to deregulated biochemical parameters in terms of folic acid, vitamin B12, calcium, bilirubin, cortisol, LDL, and total cholesterol [ 143 ]. After the diet, all these parameters significantly improved.…”
Section: Nutritional Therapeutical Strategies In Psoriasismentioning
confidence: 99%